2019
DOI: 10.1101/708735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic analysis of pathogenic isolates ofVibrio choleraefrom eastern Democratic Republic of the Congo (2014-2017)

Abstract: AbstractBackgroundOver the past recent years, Vibrio cholerae has been associated with outbreaks in Sub Saharan Africa, notably in Democratic Republic of the Congo (DRC). This study aimed to determine the genetic relatedness of isolates responsible for cholera outbreaks in eastern DRC between 2014 and 2017, and their potential spread to bordering countries.Methods/Principal f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 49 publications
2
10
1
Order By: Relevance
“…As of this writing, there are no published V. cholerae O1 genomes from the nearby countries of Benin, Burkina Faso, or Mali, for example, from after 2010. Sequences from Central African Republic, South Sudan and Democratic Republic of the Congo from 2011–2018 suggest that the T10 lineage is predominant in Central Africa (2,12), but more recent data are needed to delineate the boundary between T10 and T12 circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of this writing, there are no published V. cholerae O1 genomes from the nearby countries of Benin, Burkina Faso, or Mali, for example, from after 2010. Sequences from Central African Republic, South Sudan and Democratic Republic of the Congo from 2011–2018 suggest that the T10 lineage is predominant in Central Africa (2,12), but more recent data are needed to delineate the boundary between T10 and T12 circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-four genomes produced reference-based assemblies (covering at least 95% of the N16961 reference at >100x coverage, Appendix Table 2 ). We aligned these genomes to 1280 previously-published V. cholerae O1 whole genome sequences (1,2,11,12) and generated a maximum likelihood tree from these data, which showed that all 44 isolates belong to the T12 lineage. Two sequenced isolates did not align to the reference (NGA_148_2019, NGA_252_2019), and we found that the reads did not map to the wbe or wbf gene clusters associated with the O1 and O139 serogroups, respectively (or the ctxA cholera toxin) (13).…”
Section: The Studymentioning
confidence: 99%
“…However, so far, no V. cholerae phage has been reported to be sensitive to these two islands. Due to the prevalence of these two genomic islands in the circulating clinical isolates of V. cholerae [2,26,27], we hypothesize that novel phages that are sensitive to these islands exist and can be isolated. Therefore, we screened for novel phages from rice water stool (RWS) samples that had been collected from cholera patients in Bangladesh on permissive host, which is an O1 El Tor V. cholerae E7946 derivative lacking both VSP-I and VSP-II islands (ΔVSP) and deleted for prophages CTXΦ and K139 [28,29] .…”
Section: Isolation Of Vsp-i/vsp-ii Susceptible Phagementioning
confidence: 99%
“…Nine V. cholerae isolates were selected from a collection of isolates characterized in a recent study conducted between 2014 and 2017 in the DRC [7]. In addition, ten V. cholerae isolates collected between 2014 and 2016 in Uganda by G. Bwire and colleagues were selected based on their published data [8].…”
Section: Sample Descriptionmentioning
confidence: 99%